The Impact of Decreasing Rubber Prices on Consumption Patterns of Society from the Perspective of Islamic Economics (A Case Study in Padang Pelawi Village, Sukaraja District, Seluma Regency) - Ahmad Cholil; Romi Adetio Setiawan; Uswatun Hasanah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to find out how the consumption pattern of the people in Padang Pelawi Village was before and after the decline in the selling price of rubber and what was the Islamic economic view of the consumption patterns of the people in Padang Pelawi Village after before and after the decline in the selling price of rubber. This research uses a qualitative descriptive approach using field research types. The results of this study indicate that when the price of rubber before the decline in the consumption pattern of the people in Padang Pelawi Village could still be fulfilled properly. However, after the decline in the selling price of rubber, the consumption pattern of the people in Padang Pelawi Village was very difficult in terms of meeting their needs. Because of this, rubber farmers in Padang Pelawi Village sometimes look for other solutions, such as borrowing money from their neighbors and taking loans from food stalls. The view of Islamic economics on the consumption patterns of the people in Padang Pelawi Village is still not in accordance with Islamic consumption values. First, when the price of rubber is rising, people are often wasteful in terms of consuming something. Second, some people in Padang Pelawi Village spend their wealth only in halal forms and some people in Padang Pelawi Village also take actions that are not in accordance with Islamic teachings, namely by weighing the rubber latex so that it becomes heavy when weighed. Third, the people in Padang Pelawi village live in a luxurious style by buying expensive goods, but after that these items are no longer used.